The PICS project: II. Circumnebular extinction variations and their effect on the planetary nebula luminosity function - Valenzuela, Lucas M.; Jacoby, George H.; Remus, Rhea-Silvia; Miller Bertolami, Marcelo M.; Méndez, Roberto H. (Frontiers in Astronomy and Space Sciences, 2025)
For decades, the theoretical understanding of planetary nebulae (PNe) has remained in tension with the observed universal bright-end cutoff of the PN luminosity function (PNLF). The brightest younger PN populations have been observed to be fainter in their [OIII] emission than expected. Recent studies have proposed that circumnebular extinction is a key ingredient in bringing their brightness down to the observed level. In this work, we use the recently introduced PICS (PNe In Cosmological Simulations) framework to investigate the impact of different circumnebular extinction treatments on the modeled PNe and their PNLF for a large range of stellar ages and metallicities. We test how different slopes in the observed relation of extinction versus central star mass modify the bright-end cutoffs of the PNLF, finding that steeper slopes lead to large changes for young stellar populations. In contrast, the differences for older PNe are much smaller. However, for individual PNe, the extinctions observed in nearby galaxies appear to be much higher than the models predict, showing that improvements on both the modeling and observational sides are needed to gain a better understanding of the brightest and strongly extincted PNe. These findings further advance the theoretical foundation for interpreting observed extragalactic PN populations coming from more complex composite stellar populations in the future.